Environment (UN New YorkUS, 2000)
Focuses on international investment agreements containing environmental references. Also discusses other relevant international instruments. Addresses the following key issues: the general protection of the environment through general references to the desirability of safeguarding the environment; preserving national regulatory space for environmental protection and/or failing to attract foreign direct investment (FDI) through a lowering of environmental standards; and the transfer of environmentally sound technology and management practices.
Keywords: ENVIRONMENT